Hydroxycinnamic Acids and Their Related Synthetic Analogs: An Update of Pharmacological Activities - Selka, Ayyoub; Moutombi, Fanta J. Ndongou; Jean-François, Jacques; Touaibia, Mohamed (Mini Reviews in Medicinal Chemistry, 2022)
The hydroxycinnamic acid scaffold is extremely versatile with various biological activities. This review will highlight the progress of the biological activities of hydroxycinnamic acids and their related synthetic analogs, including recently reported anti-cancer, anti-inflammatory, and antioxidant activities.
Keywords: antioxidant